Learning and Earning: The Role of Incentives in Educational Achievement - Olga Ebert; Mary Ziegler; Gail Cope (Adult Education Research Conference, 2001)
Can external rewards develop intrinsic motivation? Based on the research projects conducted with adult basic education programs for recipients of public assistance, this roundtable will examine how incentives influence participation in educational activities and achievement of educational outcomes.